PENGEMBANGAN KECERDASAN EMOSIONAL DALAM PENDIDIKAN ISLAM - Aida Husna (AL-BURHAN, 2014)
The development Emotional Intelligence was based on the reality that shows many people with above average level of IQ could do something that can destroy them. It also can be denied that many people with average IQ live successfully. The stressing of the concept of Emotional Intelligence is how to use emotion as source of the information to solve personal problem and to be creative. This article concluded, fisrt, that Emotional Intelligence consists of potention to recognize and to manage the emotion so that this emotion not to handicap the cognitive potention. Second, there some differences between IQ and EI on their ability and also their location on the brain. Third, EI is a potention that can be developed, while EQ is the shape of its development. Finally, EI can bedeveloped through the family education at least in two ways, such as by giving a condusive environment and by giving a lesson about emotion and how two manage it.